Integrating Pragmatics into English Language Teaching: Challenges and Opportunities - Akhrif Yahsya (Educazione: Journal of Education and Learning, 2023)
Pragmatic competence has become an essential component of communicative competence in English language teaching (ELT), yet its integration into English as a Foreign Language (EFL) classrooms remains limited. This study investigates how English teachers integrate pragmatics into classroom instruction, the challenges they encounter, and the opportunities that support pragmatic instruction in Indonesian EFL contexts. Employing a qualitative descriptive design, the study involved eight English teachers from two public senior high schools in Panyabungan, North Sumatra, Indonesia, selected through purposive sampling. Data were collected through semi-structured interviews and supporting teaching documents and analyzed using Braun and Clarke's thematic analysis. The findings revealed three major themes. First, teachers integrated pragmatics through explicit instruction of speech acts, contextual role-play, authentic audiovisual materials, and discussions of pragmatic failure. Second, teachers encountered several pedagogical and contextual challenges, including limited pragmatic content in textbooks, difficulties in assessing pragmatic competence, insufficient confidence in teaching culturally embedded meanings, first-language interference, limited exposure to authentic English communication, and examination-oriented learning. Third, several opportunities facilitated pragmatic instruction, including digital technology, the flexibility of the Merdeka Curriculum, the integration of Mandailing cultural values, and collaboration through the English Teachers' Working Group (MGMP). The study concludes that although pragmatic instruction remains constrained by various structural factors, Indonesian EFL teachers demonstrate considerable pedagogical creativity in promoting communicative competence. The findings highlight the importance of strengthening teacher professional development, improving instructional materials, and incorporating pragmatic competence more systematically into English language curricula and assessment.